Membangun Budaya Menabung Dan Manajemen Keuangan Untuk Santri Pada Yayasan Rh La Tahzan Cinangka, Depok – Jawa Barat - Rini Septiowati; Habibah (CV. Multi Kreasi Media, 2025)
Community Service entitled Building a Culture of Savings and Financial Management for Students at the Rh La Tahzan Foundation in Cinangka, Depok - West Java aims to introduce and provide knowledge and understanding to students of the RH La Tahzan Foundation, Cinangka, Depok - West Java regarding the importance of having skills and financial management skills from an early age to participate in reducing poverty in Indonesia. The target of this service is students of the RH La Tahzan Foundation, Cinangka, Depok - West Java. The results of this PKM prove that students who are mostly in poverty can master financial management methods which will later provide a sense of self-confidence in selling themselves at work because they have value, are looking for work and are useful for others and ultimately can help play a role in reducing poverty in Indonesia.